Drive mechanism for Personal Transporter (PT) - Syahril Izzat Bin Azmi, Syahril Izzat (Universiti Teknologi Petronas, 2010)
Dependency on fossil-fuel transportation contributes to excessive emission of carbon dioxide gas in atmosphere. This leads to a serious environmental problem which is called global warming. Serious action has to be taken immediately by all in order to stop the problem from becoming worst. One of the effective ways to doing so is to stop depending on fossil-fuel vehicle. Thus, Personal Transporter provides an answer for this problem. There are companies such as Segway Corp., Honda and Toyota have taken advance step by producing their own transporter.